(untitled) (Challenges of the Future, 2023)
Research Question (RQ): In the article we wanted to discover if the occurrence of cyberbullying among adolescents has grown during covid-19 compared to the period before covid-19. Purpose: The aim of the article was to research if the occurrence of cyberbullying among Slovenian adolescents during the covid-19 compared to the period before covid-19. Methods: In the article we used the descriptive method, with the help of which we described the theoretical starting points. In the empirical part of the thesis, we used a quantitative method, with the help of the survey method. In the survey questionnaire the Likert scale was used, in order to measure the extent to which the respondents agree with various statements in the field of cyberbullying. Results: According to the surveyed adolescents, they rarely experienced online violence both before and during the covid-19 period, but some of the adolescents more often reported receiving messages with inappropriate content and messages that they did not want to receive and see. We also found that, compared to adolescent men, adolescent girls received messages with inappropriate content to a greater extent, which they did not want to receive and see and which made them feel afraid, and they also more often received rude and insulting comments about their appearance, others threatened them more often online. Organization: With the help of the research, we wanted to examine the frequency of cyberbullying in relation to the time before and during the covid-19, which is especially important for organizations (in this case, schools) as they take care of creating a safe and stimulating learning environment, where it is necessary to start with the prevention of this forms of violence if we want to achieve involvement and physical and psychosocial safety of the adolescents. Society: The article deals with a socially relevant topic, as it deals with the presence of violence among young people in the period between covid-19. Due to the fact that covid-19 is a relatively new challenge in the field of virology, the mentioned area currently remains under-researched, so the present research represents only the beginning of the study of the selected area. The results of the present research can be used by many experts who want to study the topic further, or by young people, parents and teachers who want to get to know the mentioned field in more detail. Originality: The originality of the article lies in the fact that it deals with a very relevant social issue, which affects the so far little-researched impact of the covid-19 era on peer bullying and cyberbullying among adolescents. Limitations/Future Research: The limitations of the research are reflected in the limitation of the studied sample and in incompletely completed questionnaires. The research could be expended to include in-depth interviews among the participants, both adolescents and parents as well as education professionals, as the quality of a school is strongly related to a safe and stimulating learning environment. As a result, this kind of a research could also be linked to the prevention of cyberbullying. Further research could allow us to understand open communication in school, which creates a stronger sense of belonging to the school, because a favorable climate can allow a school to transform into a learning community, which means building a stimulating learning environment characterized by mutual respect and trust both for students and their teachers.